Peranan Amanat Agung Tuhan Yesus Menurut Matius 28:19-20 dan Implementasinya Bagi Pendirian Jemaat Baru - Paulus Kunto Baskoro; Paulus Purwoto (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
The Great Commission of the Lord Jesus commands every believer to go and make all nations become disciples of Jesus. This is called mandate evangelism. But many of God's churches or believers are not serious in carrying out the evangelistic mandate which is God's will to bring everyone to believe in Jesus. Even when talking about evangelism, it seems something that is difficult and unpleasant, it is proven that evangelistic sermons or seminars are not very popular, and some argue that evangelism is only the job of pastors and clergy. This writing tries to provide an explanation of how important the great commission is as part of the task of believers in the movement of establishing a new church. The author uses the method of writing descriptive literature. The purpose of this paper is First, to convey the importance of an evangelism in the local church; Second, how important is the participation of all believers in establishing a new church; Third, invite every believer or church to have a clear vision to always be consistent in the establishment of new congregations.